Evaluating the influence of straw mulching and intercropping on nitrogen uptake, crop growth, and yield performance in maize and soybean - Liu, Siping; Wang, Lixue; Chang, Liang; Khan, Ismail; Nadeem, Faisal; Rehman, Abdul; Suo, Ran (Frontiers in Plant Science, 2023)
Introduction: Intercropping and straw mulching are sustainable agricultural practices that can positively affect crop growth and development, especially together. Methods: A split-plot experimental design was used to investigate the effects of intercropping and straw mulching on crop growth, crop yield, nitrogen uptake, and photosynthetic characteristics. The main plot focused on three planting patterns: soybean monoculture (S), maize monoculture (M), and maize/soybean intercropping (I). The subplot structure consisted of four levels of straw mulching (0, 4.8, 7.2, 9.6 t ha-1). Results: Interaction and variance analyses showed that straw mulching, intercropping, and their interaction had significant effects on plant height, stem diameter, leaf area index, chlorophyll content, nitrogen uptake, photosynthetic characteristics, and crop yield. Based on two-year averages for maize and soybean, the net photosynthetic rate (Pn) was up to 51.6% higher, stomatal conductance (Sc) was up to 44.0% higher, transpiration rate (Tr) was up to 46.6% higher, and intercellular carbon dioxide concentration (Ci) was up to 25.7% lower relative to no mulching. The maximum increases of Pn, Sc, and Tr of intercropped maize were 15.48%, 17.28%, and 23.94%, respectively, and the maximum Ci was 17.75% lower than that of monoculture maize. The maximum increase of Pn, Sc, and Tr of monoculture soybean was 24.58%, 16.90%, and 17.91%, respectively, and the maximum Ci was 13.85% lower than that of intercropped soybean. The nitrogen uptake of maize and soybean in the mulching treatment was 24.3% higher than that in the non-mulching treatment; the nitrogen uptake of intercropped maize was 34.2% higher than that of monoculture maize, and the nitrogen uptake of monoculture soybean was 15.0% higher than that of intercropped soybean. The yield of maize and soybean in the mulching treatment was 66.6% higher than that in the non-mulching treatment, the maize yield under intercropping was 15.4% higher than that under monoculture, and the yield of monoculture soybean was 9.03% higher than that of intercropped soybean.